Art from a Fractured Past - Milton, Cynthia (Duke University Press, 2013)
Peru's Truth and Reconciliation Commission not only documented the political violence of the 1980s and 1990s but also gave Peruvians a unique opportunity to examine the causes and nature of that violence. In Art from a Fractured Past, scholars and artists expand on the commission's work, arguing for broadening the definition of the testimonial to include various forms of artistic production as documentary evidence. Their innovative focus on representation offers new and compelling perspectives on how Peruvians experienced those years and how they have attempted to come to terms with the memories and legacies of violence. Their findings about Peru offer insight into questions of art, memory, and truth that resonate throughout Latin America in the wake of "dirty wars" of the last half century. Exploring diverse works of art, the contributors show that art, not constrained by literal truth, can generate new opportunities for empathetic understanding and solidarity.